The effect of anesthetic technique for transvaginal ultrasound-guided oocyte retrieval on reproductive outcomes: A systematic review and meta-analysis - Bharatram Vasudevan; Anuradha Borle; Preet Moinder Singh; Rashmi Ramachandran; Vimi Rewari; Anjan Trikha (Wolters Kluwer Medknow Publications, 2015)
The effects of various anesthetic techniques used for transvaginal ultrasound-guided oocyte retrieval (TUGOR) on reproductive outcomes remain controversial. Some studies have reported adverse effects due to nitrous oxide, propofol, and other general anesthetic drugs, whereas others have found them to be safe. The aim of the current meta-analysis is to pool the data available from studies comparing effects of a loco-regional technique against general anesthesia (GA)/intravenous sedation on reproductive outcomes when used for TUGOR. We searched PubMed, EMBASE, Cochrane Register, Google Scholar, and Scopus for studies that evaluated loco-regional anesthesia against GA and reported data on fertilization rate, cleavage rate, and pregnancy rate. A total of eight studies involving 1416 women undergoing TUGOR were identified. The risk of bias was high in most studies, and only two were randomized controlled trials. The loco-regional and the general anesthetic techniques used in these studies varied widely. Pooled odds ratio comparing general versus loco-regional groups for the fertilization rate was 0.939 (95% confidence interval [CI] 0.812-1.086; P > 0.05) and for the cleavage rate was 1.046 (95% CI 0.902-1.213; P > 0.05). Loco-regional anesthesia was found to be favorable to GA with regard to the pregnancy rate (pooled odds ratio was 0.701 (95% CI 0.543-0.905; P < 0.05). No serious complication was reported. Though the pregnancy rate was found to be higher in the loco-regional group, the superiority of one technique over the other cannot be confirmed based on the available quality of evidence and requires further well-conducted trials.